The victory image: Imaging Israeli warfighting from Lebanon to Gaza. (August 2019) - Galai, Yoav
This article interrogates the concept of the 'victory image' in Israel as a militarized visual economy. What began as a visual illustration of warfighting became an integral part of operational considerations. My own contribution as an embedded photographer to that economy is used as a prism for larger changes in visual politics. These changes relate to the proliferation of an actuarial gaze as the overarching ordering principle of imaging in the subsequent Gaza Wars. Instead of celebratory images of military achievements, Israeli officials opted for information visualizations to convey a sense of achievement, allowing for the continuation of the 'visual economy, ' but with Palestinian victims of indiscriminate attacks ignored.